Corruption, public procurement and political instability in Kazakhstan. Issue 1 (2nd January 2023) - Khamitov, Zhaslan; Knox, Colin; Junusbekova, Gulsara
ABSTRACT: Kazakhstan, seen as an example of political stability in Central Asia, recently descended into political turmoil. While the causes of the violence and unrest are the subject of ongoing analysis, their origins can be linked to systemic inequalities in a country rich in natural resources. Inter alia, Kazakhstan has failed to tackle insidious problems of corruption, particularly in public procurement contracts. Public procurement constitutes a significant amount of government spending in developing countries which makes it a high-risk area for corruption. Using primary data collected from small and medium-size enterprises organisations in Kazakhstan, this research finds that public officials and suppliers are complicit in corrupt practices. Intervention strategies, such as monitoring and control, have failed to tackle this problem. While the causes of recent political instability in Kazakhstan are multiple, corruption remains an underlying and persistent problem which will add to the fermenting discontent among the citizens of Kazakhstan.